Antifungal Activity of Patch Silver Nanoparticles and Chitosan with Cellulose Nanofibers Carriers against Trichophyton rubrum and Pitysporum ovale - Yuandani; Ginting, Junius Gian; Hasibuan, Poppy Anjelisa Zaitun (Talenta Publisher, 2021)
Abstract. Wounds that are not treated and are kept open will provide an entrance for microorganisms from outside that can cause infection. One of the medical needs whose demand continues to increase is wound dressings. Chitosan is known to have wound healing activity by stimulating the formation of new tissue, and silver nanoparticles have good antimicrobial activity. Silver nanoparticles and chitosan with cellulose nanofibers carrier are made in the form of patches with the ratio formula between cellulose nanofibers and chitosan/silver nanoparticles are 1:9, 2:8, 3:8, 4:7, 5:5, 6:4, 7:3, 8:2, 9:1, and 10:0 then tested the antifungal activity against Trichophyton rubrum and Pitysporum ovale for finding the best formula for antifungal activity. The analysis showed that the patch with a ratio of 6:4 had the best antifungal activity against Trichophyton rubrum (14.7Â±0.1 mm) and a 9:1 patch on the Pitysporum ovale (6.9Â±0.05 mm) gave a significant difference to negative control (p<0.05). It can be concluded that the Patches Silver Nanoparticle and Chitosan with Cellulose Nanofibers (SNCCN) carriers have good antifungal activity in the inhibitory category.